2011
DOI: 10.1136/oemed-2011-100382.196
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the quality and comparability of job coding across seven countries in the INTEROCC study

Abstract: ObjectivesIn case-control studies exposure is generally inferred from self-reported job histories coded to occupation and industry classifi cations. In the INTEROCC study, a hygienist from each of seven countries coded local jobs reported (39 613 total jobs) to assign chemical and extremely low frequency (ELF) exposures through linkage with two jobexposure matrices. To maximise the quality and comparability of coding between countries, two comparison trials were conducted. Methods After establishing guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Common coding guidelines were provided to each center in order to ensure homogeneity in the coding. An inter-rater trial was conducted at the start of coding and results were discussed with each center in a further effort to ensure consistency of coding [34]. …”
Section: Methodsmentioning
confidence: 99%
“…Common coding guidelines were provided to each center in order to ensure homogeneity in the coding. An inter-rater trial was conducted at the start of coding and results were discussed with each center in a further effort to ensure consistency of coding [34]. …”
Section: Methodsmentioning
confidence: 99%
“…Inter-rater trials were carried out to determine the reliability of the coding between different countries, which showed that the reliability was moderately increased following an initial coding trial that included a discussion of results (McLean et al, 2011). Military work was coded, when possible, to the appropriate ISCO68 occupation code.…”
Section: Coding Of Occupational Historiesmentioning
confidence: 99%
“…Common coding guidelines were provided to each center in order to foster homogeneous coding practices. An inter-rater trial was conducted at the start of coding and results were discussed with each center in a further effort to ensure consistency of coding [ 33 ].…”
Section: Methodsmentioning
confidence: 99%